Assessing the awareness mechanisms of a collaborative programming support system (2015)
The learning and teaching of Programming can benefit from the principles of Computer Supported Collaborative Learning (CSCL). With that purpose in mind, the COLLECE system was created to support synchronous collaborative programming in learning settings. Unlike other systems with similar objectives, COLLECE incorporates many elements to support group awareness. This article presents an empirical study in which the usefulness of some of the awareness mechanisms included in this system is evaluated. One of the main contributions of this work is the combination of different techniques to evaluate interactive systems, such as questionnaires, laboratory testing, heuristic evaluation, automatic logging and eye tracking techniques. The joint use of these techniques (of both a subjective and objective nature) allows us to carry out a more complete analysis of the system under study and, in particular, about its support of awareness.